Pengaruh Latihan Lempar Tangkap Bola Kasti Terhadap Keterampilan Pukulan Lob Pada Ekstrakurikuler Bulutangkis di SMA Negeri 3 Tambun Selatan - Fadilah, Ibnu Hilmi; Mahardhika, Dhika Bayu; Hidayat, Abdul Salam (Peneliti.net, 2024)
The purpose of this research is to determine the effect of baseball throwing and catching training on lob hitting skills in badminton extracurriculars at SMA Negeri 3 Tambun Selatan. The approach used in this research is a quantitative approach with experimental research methods. The population in this study were all Badminton Extracurricular participants at SMA Negeri 3 Tambun Selatan, totaling 30 students. The research sample was taken using total sampling technique. This research instrument uses the French Test measurement test which was previously created by previous researchers. The data analysis technique uses pretest posttest design. The results of the research were a pretest mean of 12.00 and a greater posttest mean = 14.33. The results of the paired sample t-test analysis with the data obtained are a significance value (2-tailed) = 0.000 less than the significance level (α) = 0.05, so H0 is rejected and H1 is accepted. So it can be concluded that baseball throwing and catching training can have an effect on improving lob hitting skills in badminton extracurricular students at SMA Negeri 3 Tambun Selatan.